Continuous-flow trapping and localized enrichment of micro- and nano-particles using induced-charge electrokinetics - Zhao, Cunlu (2020)
In this work, we report an effective microfluidic technique for continuous-flow trapping and localized enrichment of micro- and nano-particles by using induced-charge electrokinetic (ICEK) phenomena. The proposed technique utilizes a simple microfluidic device that consists of a straight microchannel and a conducting strip attached to the bottom wall of the microchannel. Upon application of the electric field along the microchannel, the conducting strip becomes polarized to introduce two types of ICEK phenomena, the ICEK flow vortex and particle dielectrophoresis, and they are identified by a theoretical model formulated in this study to be jointly responsible for the trapping of particles over the edge of the conducting strip. Our experiments showed that successful trapping requires an AC/DC combined electric field: the DC component is mainly to induce electroosmotic flow for transporting particles to the trapping location; the AC component induces ICEK phenomena over the edge of the conducting strip for particle trapping. The performance of the technique is examined with respect to the applied electric voltage, AC frequency and the particle size. We observed that the trapped particles form a narrow band (nearly a straight line) defined by the edge of the conducting strip, thereby allowing localized particle enrichment. For instance, we found that under certain conditions a high particle enrichment ratio of 200 was achieved within 30 seconds. We also demonstrated that the proposed technique was able to trap particles from several microns down to several tens of nanometer. We believe that the proposed ICEK trapping would have great flexibility that the trapping location can be readily varied by controlling the location of the patterned conducting strip and multiple-location trapping can be expected with the use of multiple conducting strips.